Decomposition rates in Cueva de Los Guacharos National Park (Huila, Colombia) (2017)
Litter decomposition studies show no consensus about the hierarchy of factors that affect the process, probably because the most important factor is not the same across sites. Clarifying this issue is relevant since global climate change may affect decomposition rates, and predictions of carbon sinks are needed. In general, decomposition rates depend mostly on climate, biota and substrate quality. The Tea Bag Index (TBI) protocol has been used recently to control for substrate quality and it has been proposed as a standardize protocol to measure decomposition rates. The aim of this paper is focused in determining the decomposition rates of 19 vegetation plots in Cueva de Los Guacharos National Park by using the TBI and Double Exponential model and compare these indices. The TBI protocol was used and several biotic and abiotic factors registered in each plot, as mean temperature, pH, organic carbon percentage, nitrogen percentage, type of forest, land use, mean slope, altitude and number of plant species were included in the analyses. No significant differences were found in decomposition rates between models, but the TBI model showed stronger limitations than the other one. Neither single or multiple liner regression showed a causal effect from environmental variables on decomposition rates, because environmental factors were similar between plots. However, we found higher rates in secondary than in primary forest, which may be associated with high temperatures or a different community of decomposers. Moisture must be included in future analyses, as well as other approaches to determine decomposition rates (the tea bags employed were of low quality and so sensitivity to factors, like temperature, is diminished)